Some Berber etymologies XIII - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper contains new etymological entries to Berber lexical roots and is part of a long-range series eventually resulting, when completed, in materials for an etymological dictionary of Berber, a desired addition to the fascicles of the comparative dictionary of Berber roots (DRB).